Bibliometric Mapping Analysis of Nanocrystalline Starch in Food Packaging Application using VOSviewer - Asep Bayu Dani Nandiyanto; Alifa Listina Dewi (Advance Sustainable Science Engineering and Technology, 2022)
Biodegradable materials needed to reduce packaging waste and extend food shelf life. Starch nanomaterials are one of the promising alternatives as environmentally friendly sustainable food packaging for single-use products. This study was to conduct a bibliometric analysis of starch nanocrystal research in food packaging applications using mapping analysis on VOSviewer software. Data was obtained from Google Scholar search which is integrated with Publish or Perish as a reference application. The data search was based on the keywords “nanocrystalline, starch, food, packaging, chemistry”. The results showed that there were 1000 articles that met the research keyword criteria with visualization showing 269 items and 10706 links divided into 8 clusters. The results of the analysis show that the number of research publications from 2012 to 2022 has increased every year until 2021. However, in 2022 the number of articles published decreased quite dramatically. This research is expected to help further researchers and be a consideration in deciding the research topic.